Management of Secondary Angle Closure Glaucoma in Nanophthalmic Eye : A Challenging Case: Poster Presentation - Case Report - Resident - Almira, Dwirianti; Umbara, Sonie (Majalah Oftalmologi Indonesia, 2023)
Introduction : Nanophthalmos is a condition characterized by short eyeball length (AXL <20.0mm), short and dense anterior segment, high eye volume or lens ratio, hypermetropia (+8.00 to +20.00) and scleral thickening (>1.7mm) Case Illustration : A 63-year-old man came to the Glaucoma outpatient clinic at Cicendo Hospital with complaints of blurry eyes since 3 years ago. The visual acuity in the right eye was light perception, and in the left eye was hand movement. The anterior chamber was shallow, with seclusio pupil in both eyes (Figure1). Biometry showed axial length 17.06 mm in the right eye and 16.82 mm in the left eye. The patient underwent phacoemulsification surgery + IOL + iris retractor + pupiloplasty + synechiolysis + sclerectomy for the right eye with satisfactory result (Figure3). Discussion : This surgical procedure for nanophthalmos has its own challenges for the operator due to the shallow anterior segment and small corneal diameter. In this case, surgery was performed first in the right eye, with consideration of a greater anterior chamber depth than the left eye. The sclerectomy procedure performed on this patient was 4 mm from the limbus and was performed full thickness only in one quadrant (Figure2). Conclusion : Multiple anatomic abnormalities in nanophthalmic eyes make surgery extremely challenging and are associated with a high incidence of significant intraoperative and postoperative complications. Phocoemulsification with sclerectomy can be alternative option to manage secondary glaucoma in nanophthalmic eye.